Dinâmica da paisagem e conectividade ecológica: uma abordagem espaço-temporal aplicada ao planejamento territorial na bacia do Búzi – Moçambique - Machava, Castigo David Augusto (Universidade Federal de São Carlos, 2026)
This study analyzes landscape dynamics and their effects on ecological connectivity in the Búzi River Basin, Mozambique, integrating spatio-temporal approaches, landscape metrics, and future scenario modeling. Chapter I establishes the conceptual foundation through a systematic literature review, demonstrating that landscape fragmentation, driven by land-use and land-cover changes, is the primary factor reducing structural connectivity. Chapter II evaluates landscape evolution from 1990 to 2024, revealing a significant increase in fragmentation associated with agricultural expansion and anthropogenic pressures. In Chapter III, prospective scenario modeling indicates that continuing current trends is likely to intensify connectivity loss, whereas sustainable strategies may mitigate these impacts. Chapter IV integrates environmental variables and resistance surfaces to model ecological connectivity, identifying priority areas for conservation and delineating ecological corridors using least-cost path analysis. Finally, Chapter V assesses connectivity under future scenarios, highlighting strategic corridors for ecological conservation. The results demonstrate that landscape connectivity is a dynamic process strongly shaped by land-use trajectories and emphasize the need for predictive and integrated approaches to support territorial planning and biodiversity conservation.
Landscape dynamics and ecological connectivity: a spatiotemporal approach to territorial planning in the Búzi river basin, Mozambique.
Keywords: Uso e cobertura do solo; Modelagem de cenários; Planejamento territorial; Bacia do Búzi; Land use and land cover; Ecological corridors; Scenario modeling; Territorial planning; Búzi river basin; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOFISICA::SENSORIAMENTO REMOTO; 13. Ação contra a Mudança Global do Clima; 12. Consumo e Produção Responsáveis; 15. Vida Terrestre